2017
DOI: 10.1155/2017/2061935
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Scores Are Associated with Amygdala Volume in Cushing’s Syndrome: Preliminary Study

Abstract: Introduction Cushing's syndrome (CS) has repeatedly been associated with hippocampal volume reductions, while little information is available on the amygdala, another structure rich in glucocorticoid receptors. The aim of the study was to analyze amygdala volume in patients with CS and its relationship with anxiety, depression, and hormone levels. Material and Methods 39 CS patients (16 active and 23 patients in remission) and 39 healthy controls matched for age, sex, and education level completed anxiety (STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Reduced amygdala volumes in comparison to controls have also been found in children with CS (66). Left amygdala volumes are negatively correlated with depression and anxiety scores in active CS (but not in patients in remission) (65). Interestingly, right cerebellar cortex volumes correlated with QoL scores, while left cerebellar cortex volumes correlated with visual memory (51).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 91%
See 1 more Smart Citation
“…Reduced amygdala volumes in comparison to controls have also been found in children with CS (66). Left amygdala volumes are negatively correlated with depression and anxiety scores in active CS (but not in patients in remission) (65). Interestingly, right cerebellar cortex volumes correlated with QoL scores, while left cerebellar cortex volumes correlated with visual memory (51).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 91%
“…For instance, smaller hippocampal volumes have been found in active patients than in controls, which have been related to learning and memory dysfunction, and also to cortisol blood levels (64). Adult patients with active disease also have smaller cerebellar cortex and right amygdala volumes than healthy controls (51,65). Reduced amygdala volumes in comparison to controls have also been found in children with CS (66).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 99%
“…Since 1998, when direct evidence for adult neurogenesis in humans first was presented, 110 hippocampal dynamics have been the focus of numerous studies. [111][112][113][114][115][116] Although the question whether there is significant adult neurogenesis remains a matter of controversy, 117 this specific region of the brain has been suggested as having an annual turnover of neurons of almost 2%. 118 Hippocampal gray matter volume alterations have been demonstrated in connection with normal physiological variability like exercise, 119 the menstrual cycle, 120 and aging 121 as well as in pathological conditions like Alzheimer's disease, 122 mild cognitive impairment, 123 post-traumatic stress disorder, 124 major depressive disorder, 125 126 Parkinson's disease, 127 and Cushing's syndrome, [112][113][114][115][116] all of which are illnesses with mental symptoms.…”
mentioning
confidence: 99%
“…Cortical brain atrophy and ventricular enlargement in patients with active CS were first described in autopsy studies [32], and later by using pneumoencephalography [33]. Since then, several studies, using modern methodology on larger cohorts, have confirmed these adverse structural effects of hypercortisolism on the brain [34‐36]. In the first studies using magnetic resonance imaging (MRI), patients with active CS were found to have decreased hippocampus volume in comparison to healthy individuals [21], and that the volume increases, but does not normalize, following remission [22,37].…”
Section: Neuroimagingmentioning
confidence: 99%
“…Cerebral atrophy has also been observed in patients with active CS, both in adults [39,40] and in children [41], which was only partially reversible following treatment. Other findings in active CS patients involve smaller volumes in comparison to healthy controls of several brain structures, including grey matter volumes of the medial frontal gyrus [42], cerebellar cortex and grey matter volumes [43], right amygdala volumes [36] and total amygdala volumes in children [41]. Furthermore, cross‐sectional studies including patients with CS in remission have demonstrated reduced cortical thickness in several regions in the prefrontal cortex [31], smaller grey matter volumes in the anterior cingulate cortex [31,44] and greater volume of the bilateral caudate nucleus [42].…”
Section: Neuroimagingmentioning
confidence: 99%